Analisis Kualitas Produk, Kepuasan Pelanggan dan Promosi terhadap Keputusan Pembelian Ulang Produk (Studi Kasus pada Larissa Skincare Jember) - Irsyandi, Achmad; Fatimah, Feti; Nursaidah, Nursaidah (BUDGETING : Journal of Business, Management and Accounting, 2024)
This study aims to analyze product quality, customer satisfaction, and the promotion concept of repurchasing decisions for Larissa Skin Care products in Jember. The type of data to be used is quantitative data. The primary data source that will be used in this study comes from a list of questions (questionnaires) that will be distributed to respondents. The questionnaire contains data on the characteristics of the respondents in the form of gender, age, profession, status, number of product purchases, number of treatments. The questionnaire also contains questions regarding the variables of product quality, customer satisfaction, promotions and repurchase decisions. The results showed that product quality has a significant effect on repurchasing decisions for Larissa Skin Care products in Jember. Then the customer has a significant effect on the repurchase decision of Larissa Skin Care product satisfaction in Jember. Lastly, promotions have a significant effect on repurchasing decisions for Larissa Skin Care products in Jember. Keywords: Customer Satisfaction, Product Quality, Promotion, Repurchasing Decisions.